2018
DOI: 10.3390/jcm7110463
|View full text |Cite
|
Sign up to set email alerts
|

Upper Normal Serum Creatinine Concentrations as a Predictor for Chronic Kidney Disease: Analysis of 14 Years’ Korean Genome and Epidemiology Study (KoGES)

Abstract: Both serum creatinine (sCr) and estimated glomerular filtration rate (eGFR) have been used to assess kidney function in public health check-ups. However, when the sCr is within the normal levels but the eGFR is <60 mL/min/1.73 m2, a dilemma arises, as the patients might progress to chronic kidney disease (CKD) after several years. We aimed to evaluate the association between normal sCr and the risk of incident CKD in the general population. For this, 9445 subjects from the Korean Genome and Epidemiology Study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 40 publications
(36 reference statements)
1
5
0
2
Order By: Relevance
“…The concentration of serum creatinine is increased by renal dysfunction. The abnormal range for male is >1.2 mg / dl and >1.0 mg / dl for females [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…The concentration of serum creatinine is increased by renal dysfunction. The abnormal range for male is >1.2 mg / dl and >1.0 mg / dl for females [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…Besides this, we also found that BFFM increases Crea levels and CKD risk. The serum Crea level was a surrogate of muscle mass (44) and has been used to assess kidney function and also as a predictor of CKD (45). However, the positive effect of BFFM on CKD may be due to higher BFFM leading to an increased Crea level, thus causing underestimated kidney function.…”
Section: Explanations and Implicationsmentioning
confidence: 99%
“…19 Según las guías de la organización Kidney Disease: Improving Global Outcomes (KDIGO) para la evaluación de la función renal en adultos, también se incluyó la CrS, 5 que en conjunto con el AU son considerados marcadores de la función renal. [8][9][10] Se definió como disminuida una TFGE <90 ml/min/1.73 m 2 . La CrS (mg/dL) y el AU (mg/dL) fueron determinados mediante el Sistema SYNCHRON-CX en las muestras séricas colectadas previo ayuno de ≥8 horas.…”
Section: Medición De La Función Renalunclassified
“…5,7 La creatinina sérica (CrS) es un metabolito del fosfato de creatina y el marcador endógeno de filtración renal más empleado. 8,9 El ácido úrico (AU) es un antioxidante plasmático metabolito de las purinas utilizado como marcador de función renal, también es considerado factor de riesgo independiente en el desarrollo y progresión de la ERC. 10,11 Estos marcadores bajo costo medidos comúnmente en la práctica clínica pueden ser de utilidad para identificar alteraciones de la función renal en población adulta en riesgo de desarrollar ERC.…”
unclassified